The Impact Of Counselling On The Dignity Of The Elderly In Singapore - Ho, Yeow Hung (2024)
The rise in Singapore’s ageing population has led its government to introduce various initiatives to lower the burden on the health sector and the national economy. As one of the primary approaches in social work, counselling addresses the issues underlying elderly individuals’ emotional management and decision-making. Regardless, elderly Singaporeans experience a lack of counselling assistance. The paucity of evidence-based data to elucidate the effects of counselling on older adults’ emotional management explains why this vulnerable population’s perspectives of counselling and advanced care planning (ACP) remain unreported. This convergent parallel mixed-method study aims to develop an intervention that optimally delivers advanced care planning (ACP) and counselling to enhance elderly Singaporeans’ emotional management and decision making. The specific objectives involved examinations of (1) perspectives regarding ACP, end-of-life care, counselling, and their impact on emotional management and decision-making, (2) accessibility and receptiveness toward counselling, and (3) competencies in emotional management among elderly individuals in Singapore. Twenty-five elderly individuals receiving care in the community via Voluntary Welfare Organisations (VWOs) were purposively sampled from the Senior Activity Centres (SACs) located in eastern Singapore to participate in the semi-structured interview.